2020
DOI: 10.3389/fbuil.2020.00006
|View full text |Cite|
|
Sign up to set email alerts
|

Numerical Simulation of the Dynamic Response of Ballasted Track Overlying a Tire-Reinforced Capping Layer

Abstract: This paper describes a 3D finite element (FE) model developed to understand the dynamic response of a ballasted track in which the underlying capping layer is reinforced using recycled rubber tires. Track deflection, the lateral spreading of ballast and vertical stress transmitted from the capping layer to the subgrade are discussed by considering the effect of reinforcement provided by these infilled tires. In this respect, the capping layer is confined and has improved damping properties. The cellular struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Hence, this research assesses and compared the stress history and deformation at particular points A, B, and C as well as measure the strain and stresses at every subsection point (ballast and sub-ballast) at various time increments, while computing the stiffness at every point and average stiffness at different times for measuring the ballast and sub-ballast's service life. Using standard dimensions and material properties of railway industries [3,13,16], an estimated primary result of the numerical analysis shows that at the start of the first hundred cycles, the settlement goes quickly (Figure 6), and then goes slowly and has a steady state value. Studies have shown that the number of load applications has a non-linear relationship with settlement of ballast.…”
Section: Numerical Simulation and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, this research assesses and compared the stress history and deformation at particular points A, B, and C as well as measure the strain and stresses at every subsection point (ballast and sub-ballast) at various time increments, while computing the stiffness at every point and average stiffness at different times for measuring the ballast and sub-ballast's service life. Using standard dimensions and material properties of railway industries [3,13,16], an estimated primary result of the numerical analysis shows that at the start of the first hundred cycles, the settlement goes quickly (Figure 6), and then goes slowly and has a steady state value. Studies have shown that the number of load applications has a non-linear relationship with settlement of ballast.…”
Section: Numerical Simulation and Resultsmentioning
confidence: 99%
“…Koch and Hudacsek [18] examined 3D dynamic effects resulting from a train passing over an area that has considerable support stiffness differences. Sun et al [16] created a 3D track/ground FEM for assessing the ballasted railway track's dynamic response involving a rubber tire-reinforced capping layer. Hendry [21] presented an analytical method and FEM for identifying alternative methods' efficacy concerning stabilising the embankment of mainline railway track between Belfast and Dublin.…”
Section: Introductionmentioning
confidence: 99%
“…Woodward et al [14] used DART3D to study ground dynamics when a train approaches the critical track velocity. Further 3D models based on the Ledsgård case were developed by using Abaqus [19,36,37] and Midas-GTS [38]. A 3D model utilising infinite elements and implementing absorbing boundary conditions of Lysmer and Kuhlemeyer [39] was developed by Connolly et al [40,41] and was validated using field recordings of the high-speed line Paris-Brussels and the mixed passenger and freight line Edinburgh-London, respectively.…”
Section: Track Modelsmentioning
confidence: 99%
“…This method reduces the simulation CPU times of a moving load compared to the user-subroutine defined moving loads. This method was used for a multi-car X2000 train by Shih et al [53] and Sun [37] to develop 3D models of the Ledsgård track case. In this research, a similar method developed by Shih et al [36] is implemented for the sake of computational efficiency and results accuracy.…”
Section: Vehicle Models and Moving Loadsmentioning
confidence: 99%